The development of family counseling in Jordan: a comparative perspective - Sabreen (Moh'd Alsaber) Hussein Alsaf (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study addressed the Family Counseling concept, objectives, methods, and stages of development globally and in Jordan. The study has concentrated on finding the differences between the practicing of Family Counseling globally and in the Jordan society. The study adopted the Descriptive-analytical and comparative approachto achieving the study objectives.The most important findings were that: there is a similarity between the methods and objectives of Family Counseling globally,and its methods and objectives in Jordan, also a similarity between development stages of Family Counselingglobally and in Jordan.The differences between them emerged in the professional practice as it was globally organized and confused in Jordan. The results also showed that Family Counseling globally emerged in the 1940s and 1950sof the 20th centuryand emerged in Jordan at the beginning of the 21st century.